The Mediating Role of Lifestyle in The Influence of Perceived Behavioral Control on Coffee Consumption Behavior at Tulungagung Community - Junari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The study analyzed the mediating role of lifestyle in the influence of perceived behavioral control on the coffee consumption behavior of the Tulungagung community. Method Design and Sample: This quantitative study employs an explanatory research approach using a survey method, considering the research problems and objectives. The questionnaire was developed based on the research variables, namely perceived behavioral control, consumption behavior, and lifestyle. Data were collected from 100 respondents who constituted the study sample. Data collection was conducted using random sampling among coffee shop visitors in Tulungagung Regency, East Java, Indonesia. Data analysis was performed using the Partial Least Squares (PLS) approach with SmartPLS software. Results: The hypothesis testing results indicate that both lifestyle and perceived behavioral control (PBC) have a significant effect on consumption behavior. The analysis shows that lifestyle positively affects consumption behavior, meaning that the higher a person’s lifestyle, the higher their consumption behavior. Additionally, PBC positively influences both lifestyle and consumption behavior, indicating that higher PBC corresponds to higher lifestyle and consumption behavior. Furthermore, the study found that PBC has an indirect effect on consumption behavior through lifestyle, suggesting that PBC can influence consumption behavior indirectly by enhancing lifestyle. These findings highlight the importance of considering psychological and behavioral factors in understanding individual consumption behavior. The study’s implications suggest that marketers can develop more effective marketing strategies by taking into account consumers’ lifestyle and perceived behavioral control. Moreover, the research can increase consumer awareness of the factors affecting their consumption behavior, enabling them to make more informed decisions.